2017
DOI: 10.1002/slct.201702473
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dot Assemblies for Enhanced Cellular Uptake and Photothermal Therapy In Vitro

Abstract: Constructing complex nanoarchitectures via self-assembly with nanoparticle building blocks is a practical strategy that produces nanostructures with properties that are absent in the individual unit. In this work, we used hydrophilic carbon dots (C-dots) as building blocks to form C-dot assemblies. Compared to the individual C-dot, the self-assembled C-dots showed about 30 nm red-shift of absorption, resulting in the 5.1% increasing of photothermal conversion efficiency upon a 671 nm laser irradiation. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, they can be exploited for multiple applications in the theranostic field, allowing imaging and phototherapy at the same time, making them more suitable with respect to other common organic dyes for bioimaging applications [103,104]. This technique is based on two features of materials that, when exposed to light at a specific wavelength (photosensitizers), generate cytotoxic reactive oxygen species (ROS, photodynamic therapy, PDT) [105] or heat (photothermal therapy, PTT) [106], capable of killing cells by photoablation. Since photosensitizers are generally harmless without light, tumor treatment can be specifically targeted by selective illumination, limiting damage to surrounding healthy tissues.…”
Section: Brain Tumor Phototherapy With Gqdsmentioning
confidence: 99%
“…Therefore, they can be exploited for multiple applications in the theranostic field, allowing imaging and phototherapy at the same time, making them more suitable with respect to other common organic dyes for bioimaging applications [103,104]. This technique is based on two features of materials that, when exposed to light at a specific wavelength (photosensitizers), generate cytotoxic reactive oxygen species (ROS, photodynamic therapy, PDT) [105] or heat (photothermal therapy, PTT) [106], capable of killing cells by photoablation. Since photosensitizers are generally harmless without light, tumor treatment can be specifically targeted by selective illumination, limiting damage to surrounding healthy tissues.…”
Section: Brain Tumor Phototherapy With Gqdsmentioning
confidence: 99%
“…The CuCDs nanosheets exhibited laser-triggered cytosolic delivery, lysosomal escape and nuclear-targeting nature. To enhance the cellular uptake or the EPR, Hou et al [183] conjugated the carboxylate CDs with PLGA-b-PEG-NH 2 through growth curves (n = 5) observed after different treatments (n = 5, P < 0.05 for each group); (g) the relative body weights of the nude mice increased continuously after different treatments; (h) representative photographs of the four groups after different treatments; (i) H&E stained images of tumors of the four groups after different treatments [150]. Reproduced from [11] with permission of The Royal Society of Chemistry.…”
Section: Fluorescent Cds Conjugated With Photothermal Therapeutic (Ptmentioning
confidence: 99%
“…Interestingly, Hou et al showed that PEG coating causes the red-shift of the fluorescence emission of CDs. These red emissive carbon dot assemblies demonstrated a higher PCE for in vitro eradication of cancer cells than their uncoated individual counterparts ( Hou et al, 2017 ). Additionally, specific chemical and physical modifications narrow the HOMO-LUMO band gap, redshifting the fluorescence emission peak and improving their photothermal performance ( Masha and Samuel Oluwafemi, 2022 ).…”
Section: Photothermal Applicationsmentioning
confidence: 99%